QUAT—a Tool for Evaluating the Quality of Core Assessments in Child-Protection Investigations. (24th December 2018) - Karlsson, Henrik; Avby, Gunilla; Svendsen, Tore
Abstract: This article presents a quantitative tool for evaluating the documentation quality of core assessments in child-protection investigations called the Quality Assessment of the Triangle (QUAT). QUAT measures compliance with a set of quality standards for working with the Swedish adaptation of the British Integrated Children's System (ICS), and should be viewed as an attempt to further the UK-led efforts to improve child-protection investigations by promoting research-based documentation systems. This article describes how QUAT was developed and later applied to a random sample of case files provided by the social services in Stockholm City, Sweden, to demonstrate its usability in practice. The contribution of QUAT is two-fold: first, it offers a way for managers to stimulate workplace learning by providing continuous feedback on the documentation and, second, it may help researchers to evaluate the effectiveness of interventions aiming to improve professional performance in terms of documenting child-protection investigations.